PENGUJIAN DAYA HAMBAT EKSTRAK BEBERAPA TUMBUHAN TERHADAP JAMUR CERATOCYSTIS SP. PENYEBAB PENYAKIT BUSUK BERAIR PADA BUAH SALAK BALI - SUNITI, NI WAYAN (AGRITROP, 2007)
The research aimed to determine the inhibition activity of some plant extracts against Ceratocystis sp. on PDA medium, salacca piece, whole fruit and liquid medium. Research?s result showed that among nine plant extracts, two extracts inhibited the growth of Ceratocystis effectively, namely extract of Albinia galanga rhizome and boiled papaya leaf. Albinia galanga rhizome showed inhibitory 92.5 % on PDA medium and 89.6% on PD Broth liquid medium. Boiled papaya leaf extract showed 73.3% on PDA medium and 57.7 % on PD Broth liquid medium. On fruit piece and whole fruit inhibition activity of boiled papaya leaf extract has higher than to Albinia galanga rhizome extract.